Popcorn Inspired Porous Macrocellular Carbon: Rapid Puffing Fabrication from Rice and Its Applications in Lithium–Sulfur Batteries. Issue 1 (1st September 2017) - Zhong, Yu; Xia, Xinhui; Deng, Shengjue; Zhan, Jiye; Fang, Ruyi; Xia, Yang; Wang, Xiuli; Zhang, Qiang; Tu, Jiangping
Abstract: The advancement of electrochemical energy storage is closely bound up with the breakthrough of controllable fabrication of energy materials. Inspired by a popcorn fabrication from corn raw, herein a unique porous macrocellular carbon composed of cross‐linked nano/microsheets by a powerful puffing of rice precursor is described. The rice is directly puffed with a volume enlargement of ≈20 times when it is instantaneously released from a sealed environment with a high pressure of 1.0 MPa at 200 °C. Interestingly, when metal (e.g., Ni) nanoparticles are embedded in the puffed rice derived carbon (PRC), high‐quality PRC/metal composites are achieved with attractive properties of a high electrical conductivity of ≈7.2 × 10 4 S m −1, a large porosity of 85.1%, and a surface area of 1492.2 m 2 g −1 . The PRC/Ni are employed as a host in lithium–sulfur batteries. The designed PRC/Ni/S electrode exhibits a high reversible capacity of 1257.2 mA h g −1 at 0.2 C, a prolonged cycle life (821 mA h g −1 after 500 cycles), and enhanced rate capability, much better than other counterparts (PRC/S and rGO/S). The excellent properties are attributed to the advantages of PRC/Ni network with a high electrical conductivity, strong adsorption/blocking ability for polysulfides, and interconnected porous framework. Abstract : A unique porous microcellular carbon composed of cross‐linked nano/microsheets created by a powerful puffing of a rice precursor is described. Because of the advantages of the puffed‐rice‐derived carbon/Ni network with a high electrical conductivity and strong adsorption/blocking ability for polysulfides, the microcellular carbon‐based electrode exhibits high sulfur utilization, long cycling life, and high rate performance in a working lithium–sulfur battery.